The Theory of Signs in Port-Royal Logic - Martín, Javier Pamparacuatro (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
In the present paper we will examine the semiology in a French 17th century work: Antoine Arnauld and Pierre Nicole’s La logique ou l’art de penser (1662-1683). In this book a developed theory of sign is proposed for the first time. The present article analyzes the definition, structure, characteristics and classification of signs in Arnauld and Nicole’s theory. We will show that the Port-Royal approach is motivated by a theological controversy: the defence against the Calvinists of the Transubstantiation dogma. Starting from the defence of the literal sense of the Eucharist and from their views on language, and mirroring the Christian conception of Revelation and Salvation, the authors of the Port-Royal Logic, very influenced by the Augustinian tradition, divide signs into two radically heterogeneous spheres: the scope of worldly reality, which we know through the unavoidable mediation of signs, that is to say, the deciphering, and the Christian signs, not interpretable or decipherable.